The Effect of Changes in Organizational Structure on Employee Performance with Employee Perceptions as a Mediating Variable - I Made Suarsa; I Gede Putu Kawiana; Ida I Dewa Ayu Yayati Wilyadewi (UNHI Press, 2024)
Purpose – The aim of this research is to analyze the effect of changes in organizational structure on employee performance with employee perceptions as a mediating variable. Methodology - The population in this study was all permanent employees of Perumda Air Minum Tirta Mangutama. The sample was determined using the Slovin formula with the sampling technique used was proportional stratified random sampling, so that 75 respondents were obtained. The data analysis method used was Structural Equation Model-Partial Least Square (SEM-PLS) analysis. Findings – The research results show that changes in organizational structure have a positive and significant effect on employee perceptions, changes in organizational structure have a positive and significant effect on employee performance, and employee perceptions have a positive and significant effect on employee performance. For the mediating influence of employee perceptions, the results show that employee perceptions act as a partial mediator on the influence of changes in organizational structure on employee performance.